2017
DOI: 10.1103/physrevd.96.126006
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic universality in F-theory compactifications

Abstract: We study universality of geometric gauge sectors in the string landscape in the context of Ftheory compactifications. A finite time construction algorithm is presented for 4 3 × 2.96 × 10 755 Ftheory geometries that are connected by a network of topological transitions in a connected moduli space. High probability geometric assumptions uncover universal structures in the ensemble without explicitly constructing it. For example, non-Higgsable clusters of seven-branes with intricate gauge sectors occur with prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
160
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(167 citation statements)
references
References 33 publications
4
160
0
Order By: Relevance
“…For explicit constructions of these dualities and more details see for instance. [17][18][19][20] Note that the reduced calculational complexity required to calculate the Yukawa couplings in the dual frame was mentioned in [21].…”
Section: Hydrodynamic Transport Coefficients For Quark Gluon Plasmamentioning
confidence: 99%
“…For explicit constructions of these dualities and more details see for instance. [17][18][19][20] Note that the reduced calculational complexity required to calculate the Yukawa couplings in the dual frame was mentioned in [21].…”
Section: Hydrodynamic Transport Coefficients For Quark Gluon Plasmamentioning
confidence: 99%
“…12 It may be useful to reduce the basis for the lattice spanned by the t i . 13 And vice-versa, modulo those related by m ↔ −m, as the P -cube grid and N -parallelepiped domains in Σ are symmetric under the reflection about any of the P Cartesian coordinate axes.…”
Section: Jhep11(2017)036mentioning
confidence: 99%
“…Axions were originally proposed to solve the strong CP problem of QCD [1], and many (∼ 100) axions often arise in compactifications of string theory (see e.g. [2][3][4][5][6][7][8][9][10][11][12]). Axions can be dark matter [13][14][15][16][17], drive inflation [18][19][20][21][22][23][24] and (similar to quantized fluxes [25]) can account for the observed vacuum energy [26].…”
Section: Introductionmentioning
confidence: 99%
“…In [1], which introduced computational complexity into studies of the string landscape, it was shown that a version of the Bousso-Polchinski model [2] for the cosmological constant is NP-complete. Furthermore, computing the scalar potential in string theory, finding its critical points, and establishing that they are metastable vacua all require solving NP-hard or co-NP-hard problems [3]. Within the last two years, machine learning was introduced into the study of string theory problems [4][5][6][7] to make progress on computationally hard problems.…”
Section: Introductionmentioning
confidence: 99%
“…For physics examples, the question can be posed of how the Universe "found" the state it is currently in if this requires solving a hard or undecidable problem. For instance, when applied to finding a small cosmological constant in an eternally inflating universe [1,3,[14][15][16], this gives a measure that differs significantly from others [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%